Entry Point Safe Zone for Anteroposterior Screws in Posterior Malleolus Fracture Fixation: A Cadaver Study. Issue 4 (16th October 2019) - McKissack, Haley; Yu, Jonathan; He, Jun Kit; Montgomery, Tyler; Moraes, Leonardo; Dahlgren, Nicholas; Shah, Ashish
Category: Ankle, Basic Sciences/Biologics, Trauma Introduction/Purpose: Percutaneous anterior-posterior (AP) screw is an option for posterior malleolus fracture fixation when the fracture fragment can be reduced indirectly by the means of ligamentotaxis. However, anterior anatomic structures could be injured during screw placement. We assessed this risk in cadavers. Methods: Eleven below-knee cadavers were employed for the placement of AP screws in an attempt of fixing assumed Haraguchi Type-I posterior malleolar fractures. Three entry point, medial, middle, and lateral, were selected as medial to the tendon of tibialis anterior (TAT), lateral to the TAT, and lateral to the extensor digitorum longus (EDL). On each cadaver, three AP screws were placed under the guidance of fluoroscopy. After dissection, measurements were made (mm) from each screw to nearby structures. Mean, minimum, maximum distances, and 95% confidence intervals were calculated. Instances of damage to the structures were recorded. Results: Mean, minimum, and maximum distances from the medial screw to the saphenous vein, TA, EHL, anterior tibial artery (ATA), and deep peroneal nerve (DPN), were 18.1 (12-25) mm, 2.0 (0-5) mm, 13.6 (9-20) mm, 16.6 (9-25) mm, and 20.1 (12-27) mm. From the middle screw to the ATA, DPN, TA, EHL, and EDL, were 1.2 (0-3) mm, 4.9 (3-9) mm, 3.8 (1-7) mm, 0.4 (0-2) mm, and 13.6 (10-18) mm. From the lateral screw to the superficial peroneal nerve (SPN), EDL, DPN, and ATA, were 10.8 (0-16) mm, 1.2 (0-4) mm, 15.9 (11-25) mm, 19 (15-27) mm. The SPN was found partially cut by the lateral screw on 1 specimen. The middle screws were adjacent to the ATA and DPN without damaging to them. Conclusion: Lateral and middle percutaneous AP screw placement put certain anatomic structures at-risk of injury. Medial screw placement did not result in appreciable damage to adjacent structures. Entry point of AP screws should be selected with respect to posterior malleolar fracture and anatomic structures. Meticulous dissection should be performed when placing anteroposterior screws.